Princípios norteadores para o planejamento de cursos de línguas para propósitos específicos em curso superior tecnológico (manutenção de aeronaves): considerando visões de aprendizes, instituição formadora e empregadores - Terenzi, Daniela (Universidade Federal de São Carlos, 2014)
The technological higher education has expanded significantly in Brazil and there is a connection between the world of science and technology and the English language (CELANI, 2008). The technological higher education context, therefore, provides a rich environment for investigations considering the language teaching process, especially English. Actions are needed to adjust language teaching to the requirements of this context (ALMEIDA FILHO, 2008). Commonly, studies on needs analysis, which guide the planning of language courses for specific purposes, focus exclusively on the perspective of learners but, at the beginning of their undergraduate program, these needs may not be clear to them (ANTHONY, 1997; AUGUSTO-NAVARRO et al, 2012). Bearing that in mind, our research aims at discussing the planning of English for specific purposes courses in higher education, taking into account three perspectives: the educational institution, based on its official documents (program and syllabus); learners, considering their interests and perceptions of needs and, finally, the labor market, represented by employers of companies that hire the professionals who graduate from the technological program in focus: Aircraft Maintenance Technology. Data collection was performed using questionnaires and document analysis. The results show that there are similarities and differences, especially between the expectations of learners and the demands of the labor market compared to the objectives presented in the syllabus. Based on the obtained results and on theoretical issues considering language teaching for specific purposes discussed by many authors, we present principles aiming at sensitizing and guiding professionals involved in language for specific purposes course planning.
Keywords: Língua inglesa - ensino; Ensino de línguas para propósitos específicos; Análise de necessidades e interesses; Ensino superior tecnológico; Princípios para ELPE; Teaching languages for specific purposes; Needs and wants; Technological higher education; Principles in ESP; LINGUISTICA, LETRAS E ARTES::LINGUISTICA